Posterior percutaneous endoscopic versus traditional surgery for cervical disc herniation: A protocol for systematic review and meta analysis. Issue 31 (31st July 2020) - Sun, Feng-Qi; Wen, Shao-Jin; Ye, Bing-Lin; Li, Chen-Xu; Fan, You-Fu; Luo, Yong-Sheng; Wang, Xiang-Fu
Abstract: Background: Posterior percutaneous endoscopic cervical diskectomy (P-PECD) can be used posterior microdiscectomy for cervical disc herniation. But only some small sample sizes of clinical studies have evaluated the efficacy and safety of P-PECD. This study aim to evaluated the efficacy and safety of P-PECD compared with traditional open surgery. Methods: We will search the following seven electronic databases from their initiation to the May 1, 2020: PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM) and Wanfang database. All randomized controlled trials, non-randomized controlled trials and retrospective case controls that compared the efficacy and safety of P-PECD and traditional open surgery in the treatment of cervical disc herniation will be included. The pooled odds ratio with 95% credible intervals (CIs) was used for the dichotomous variables. The mean difference with 95% CIs was used for the continuous variables. All analyses were conducted by Comprehensive Meta Analysis 2.0. A 2-tailed P value < 0.05 is considered statistically significant. Results: The results of systematic review and meta-analysis will be submitted to a peer-reviewed journal. Conclusion: Our study will provide clarity regarding for clinicians to choices best surgical approach for patients with cervical disc herniation. Any changes that need to be made during the process of this study will be explained in the final full-text publication. Protocol registration number: CRD42020164011.